Zomato: repositioning amid COVID-19 - Suresh, K. G. (Henry Stewart Talks, 2022)
This case study looks at Indian restaurant aggregation and food delivery startup Zomato, how they adjusted operations during COVID-19 to rebrand themselves in a time of crisis.